Permafrost thaw and intense thermokarst activity decreases abundance of stream benthic macroinvertebrates - Krista S. Chin; Jennifer Lento; Joseph M. Culp; Denis Lacelle; Steven V. Kokelj (Global Change Biology, 2016)
Intensification of permafrost thaw has increased the frequency and magnitude of large permafrost slope disturbances (mega slumps) in glaciated terrain of northwestern Canada. Individual thermokarst disturbances up to 40 ha in area have made large volumes of previously frozen sediments available for leaching and transport to adjacent streams, significantly increasing sediment and solute loads in these systems. To test the effects of this climate‐sensitive disturbance regime on the ecology of Arctic streams, we explored the relationship between physical and chemical variables and benthic macroinvertebrate communities in disturbed and undisturbed stream reaches in the Peel Plateau, Northwest Territories, Canada. Highly disturbed and undisturbed stream reaches differed with respect to taxonomic composition and invertebrate abundance. Minimally disturbed reaches were not differentiated by these variables but rather were distributed along a disturbance gradient between highly disturbed and undisturbed sites. In particular, there was evidence of a strong negative relationship between macroinvertebrate abundance and total suspended solids, and a positive relationship between abundance and the distance from the disturbance. Increases in both sediments and nutrients appear to be the proximate cause of community differences in highly disturbed streams. Declines in macroinvertebrate abundance in response to slump activity have implications for the food webs of these systems, potentially leading to negative impacts on higher trophic levels, such as fish. Furthermore, the disturbance impacts on stream health can be expected to intensify as climate change increases the frequency and magnitude of thermokarst.